Experiences in developing national science and technology programs in some countries of the world - Hai, Ha Cong; Anh, Nguyen Lan; Hong Ngoc, Cao Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
The national science and technology (S&T) program is a S&T task formed to solve S&T problems in order to bring great benefits to socio-economic and S&T development of each country. In general, national S&T programs are associated with the implementation of the country’s priority S&T orientation. In Vietnam, over the past years, national S&T programs have played an important role in strengthening S&T capacity, enhancing competitiveness, contributing to promoting the country’s socio-economic development. There are many factors affecting the performance of the national S&T program, of which the development of the S&T program plays an important role. On the basis of researching experiences of developing national S&T programs of some countries, this paper draws reference lessons for Vietnam in developing national S&T programs in the coming time. Code: 20122102